(untitled) (Itinerarios Educativos, 2024)
Language reflexivity is a common property to speaking and writing activities. However, it is more recurrently related to writing practices. This paper proposes the concept of knowing how to speak, associated to a specific metalanguage of public speech that is concretized in formal oral genres, whose delimitation is seen as a possibility to know and reflect on oral linguistic practices with their own conceptual instruments, as well as to project the development of people’s discursive–textual capacity from articulating instances of oral textual production and metalinguistic thought. The class constitutes, from the speakers’ thought, a space for theorization due to the particular form that the dialogue between teachers and students assumes.